Researches on MEMS thermoelectric-photoelectric integrated energy harvester with metal heat sink. (February 2020) - Ji, Sichao; Liao, Xiaoping
Abstract: We propose a harvester based on the micro-electro-mechanical system (MEMS) and complementary metal-oxide-semiconductor (CMOS). The harvester has been integrated on a silicon substrate. In order to achieve an improved performance, the fabrication of the proposed harvester in this paper is amended to reduce the thermal resistance between the device and the environment. The device consists of two parts: thermoelectric and photoelectric. A metal heat sink made with gold is utilized at the centre of thermopiles to optimize the heat path and to enhance the thermal coupling between the harvest and surroundings. The output voltage and power are measured by a Keithley 2700. The results show that the output voltage factor and output power factor of the thermoelectric harvester are 0.5763 V cm −2 ·K −1 and 2.757 × 10 −2 μW·cm −2 ·K −2, respectively. In addition, the photoelectric harvester is realized by back-contact technology. The light receiving surfaces can be both the top and bottom side, and the corresponding efficiencies of the photoelectric harvester are 5.446% and 0.2749%, respectively.